2014
DOI: 10.1152/ajpgi.00260.2013
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis-induced fetal gut injury is mediated by direct gut exposure of inflammatory mediators or by lung inflammation

Abstract: Wolfs TG, Kramer BW, Thuijls G, Kemp MW, Saito M, Willems MG, Senthamarai-Kannan P, Newnham JP, Jobe AH, Kallapur SG. Chorioamnionitis-induced fetal gut injury is mediated by direct gut exposure of inflammatory mediators or by lung inflammation. Am J Physiol Gastrointest Liver Physiol 306: G382-G393, 2014. First published January 23, 2014; doi:10.1152/ajpgi.00260.2013.-Intra-amniotic exposure to proinflammatory agonists causes chorioamnionitis and fetal gut inflammation. Fetal gut inflammation is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 43 publications
(54 reference statements)
5
48
0
Order By: Relevance
“…The current findings confirm and explain our earlier observations, showing that local exposure of the intestinal epithelium to LPS induces lymphocyte influx and impaired gut integrity. 15 In line with these data, in vitro experiments with intestinal epithelial cells have shown that IL-1 supplementation in the culture system increased the permeability of tight junctions. 32,33 These findings indicate that increased intestinal IL-1α levels directly interact with the intestinal epithelial cells and/or resident immune cells to induce adverse intestinal outcomes as seen in the fetal intestine in the course of chorioamnionitis.…”
Section: Il-1α-driven Fetal Gut Inflammationmentioning
confidence: 63%
See 4 more Smart Citations
“…The current findings confirm and explain our earlier observations, showing that local exposure of the intestinal epithelium to LPS induces lymphocyte influx and impaired gut integrity. 15 In line with these data, in vitro experiments with intestinal epithelial cells have shown that IL-1 supplementation in the culture system increased the permeability of tight junctions. 32,33 These findings indicate that increased intestinal IL-1α levels directly interact with the intestinal epithelial cells and/or resident immune cells to induce adverse intestinal outcomes as seen in the fetal intestine in the course of chorioamnionitis.…”
Section: Il-1α-driven Fetal Gut Inflammationmentioning
confidence: 63%
“…13,14 The first signs of intestinal inflammation were detected 2 days after IA delivery of LPS, and this inflammatory response resulted from direct LPS exposure to the gut and pulmonary-induced systemic inflammation. 15 Importantly, inhibition of IL-1 signaling with an IL-1 receptor antagonist in our chorioamnionitis model largely prevented fetal organ inflammation and its negative sequelae. 16,17 IL-1 signaling is central to antenatal inflammation in multiple animal models, [18][19][20] and IA IL-1α administration in fetal sheep caused inflammation in the chorioamnion with injury to the respiratory and gastrointestinal tract.…”
mentioning
confidence: 84%
See 3 more Smart Citations